2022
DOI: 10.3390/s22082890
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Scatterometer System for Measuring Physical Oceanographic Parameters Using Range-Doppler FMCW Radar

Abstract: A multifunctional scatterometer system and optimized radar signal processing for simultaneous observation of various physical oceanographic parameters are described in this paper. Existing observation methods with microwave remote sensing techniques generally use several separate systems such as scatterometer, altimeter, and Doppler radar for sea surface monitoring, which are inefficient in system operation and cross-analysis of each observation data. To improve this point, we integrated separate measurement f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…After the radiation and the subsequent reflection of the carrier signal from the ground, this signal is received by the receiving antenna. From there, it is processed to a balanced mixer, which is at the receiver’s input [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the radiation and the subsequent reflection of the carrier signal from the ground, this signal is received by the receiving antenna. From there, it is processed to a balanced mixer, which is at the receiver’s input [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…All this has a negative effect on determining the value of the methodological error and, consequently, on the height measurement accuracy. We know from practice that, at present, it is not possible to evaluate a methodological error in the standard conditions of the operator [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This section presents the property of the ocean observation data collected by the self-manufactured multifunctional scatterometer in the previous study [ 11 ], as shown in Figure 1 and Table 1 . This section briefly shows the vulnerability of the existing analysis method based on the radar-received signal strength through the radiometric responses and linear regression analysis for each incident angle, where the observation data were measured under the sea surface condition of less than WMO (world meteorological organization) sea state code 3 (i.e., it is less than 1.25 m of wave height and the capillary wave dominant) was used [ 21 ].…”
Section: Features Of Sea Surface Observation Data (By the Existing Me...mentioning
confidence: 99%
“…However, the ground-based system that has developed into customized systems through various field campaigns has high potential in terms of utilization. It is, namely, possible to implement a cost-effective system for specialized observation in a specific area and even measure various radar parameters, such as radar backscatters, distance (or depth), and Doppler frequency simultaneously [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation